Distributed trust management scheme based on blockchain in Internet of vehicles - Haibo ZHANG; Yukun CAO; Kaijian LIU; Ruyan WANG (Tongxin xuebao)
Aiming at the security problems caused by the low efficiency and accuracy of malicious vehicle identification in Internet of vehicles, a distributed trust management scheme based on blockchain in Internet of vehicles was proposed.A false information identification strategy was designed by aggregating the scoring information of vehicles, combined with Bayesian inference model.A reputation value updating algorithm was designed by combining the historical interaction information of vehicles and traffic information, malicious vehicles were identified by the reputation threshold.A blockchain was constructed roadside units to realize the distributed storage of traffic data and vehicle reputation values.The traditional proof of work consensus mechanism was improved to dynamically change the difficulty of miner node generating a block through the event level and the number of vehicles involved in scoring, and the waiting mechanism was used to temporarily stop the nodes that had recently blocked from participating in the election process of miner nodes, thus reducing the resource consumption caused by repeated calculations.The simulation results show that the proposed scheme can effectively identify false information, resist the deceptive behavior of malicious vehicles, improve the identification efficiency of malicious vehicles, reduce resource consumption, and is effective and feasible in distributed trust management for Internet of vehicles.